The influence of Shopee's flash sale and "free shipping" tagline on the purchasing decisions of students at the Faculty of Economics, Bangka Belitung University - Astria Turnip (Journal on Economics, Management and Business Technology, 2023)
This research aims to analyze and determine the study of the influence of Shopee's Flash Sale and "Free Shipping" tagline on the purchasing decisions of students at the Faculty of Economics, Bangka Belitung University. This research is descriptive research. The method used is a quantitative method. The number of samples in this research was 90 respondents using non-probability sampling techniques. The analysis models used are data quality tests (validity and reliability), classical assumption tests (normality, multicollinearity and heteroscedasticity), multiple linear regression tests and hypothesis tests (T test, F test and R 2 test). Based on multiple linear regression analysis, it was found that Y = 7.282 + 0.568X1 + 0.655X2, the results of research on flash sales and the tagline "free shipping" partially had a positive and significant effect on the purchasing decisions of students at the Faculty of Economics, Bangka Belitung University. Simultaneous test results show that the flash sale and Shopee's "free shipping" tagline together have a positive and significant influence on the purchasing decisions of students at the Faculty of Economics, Bangka Belitung University. The results of the analysis of the coefficient of determination (R2) show that the determination of R2 in this study is 71.6% and there are still 28.4% remaining variables outside the research that can still be developed for subsequent research. Simultaneous test results show that the flash sale and Shopee's "free shipping" tagline together have a positive and significant influence on the purchasing decisions of students at the Faculty of Economics, Bangka Belitung University. The results of the analysis of the coefficient of determination (R2) show that the determination of R2 in this study is 71.6% and there are still 28.4% remaining variables outside the research that can still be developed for subsequent research